2017
DOI: 10.1186/s13071-017-2351-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of Anopheles hyrcanus group members based on ITS2 rDNA

Abstract: BackgroundThe Anopheles hyrcanus group includes 25 species, and is widely distributed in the Oriental and Palaearctic regions. Several species within this group are vectors of malaria, lymphatic filariasis and Japanese encephalitis. It is difficult or impossible to identify cryptic species based on their morphological characteristics, with some closely related species of the Hyrcanus Group have similar adult morphological characteristics. Thus, their molecular identification has been an important complementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 49 publications
7
38
0
Order By: Relevance
“…hyrcanus from An . pseudopictus , which is in accordance with a previous report [ 33 ]. Regarding the current genetic analyses, we agree with previous suggestions not to consider An .…”
Section: Discussionsupporting
confidence: 94%
“…hyrcanus from An . pseudopictus , which is in accordance with a previous report [ 33 ]. Regarding the current genetic analyses, we agree with previous suggestions not to consider An .…”
Section: Discussionsupporting
confidence: 94%
“…After collection, mosquitoes were identified using morphological characteristics according to the national key [ 38 ]. Some morphological confused specimens were determined by molecular methods, as reported previously [ 39 , 40 ]. Mosquitoes were then pooled by species, sex, and date and location of collection, with one to 50 individuals per pool.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that ITS2 would be more reliable than COI as a phylogenetic analysis tool among very close taxa. This discrepancy could be attributed to the fact that the Hyrcanus Group includes at least 25 species widely distributed in a large geographic area [15,16]. Discrepancies between markers are expected since there are different evolutionary processes that act differently on mitochondrial and nuclear genes [44].…”
Section: Discussionmentioning
confidence: 99%
“…Another information gap in Honduras is the lack of molecular data that support the classi cation of mosquitoes based on morphometric keys. Molecular markers are critical to distinguish between evolutionarily close or cryptic species, even using immature specimens [15,16].…”
Section: Introductionmentioning
confidence: 99%